BINCANG SEHAT SEBAGAI UPAYA PENCEGAHAN SEKS BEBAS DIKALANGAN REMAJA (FREE SEKS BUKAN TIPE KU : AKU CEGAH AKU AMAN) - Nelyta Oktavianisya; Yulia Wardita; Laylatul Hasanah; Sugesti Aliftitah (P3M Politeknik Negeri Malang, 2025)
Free sex behavior is one of the serious problems faced by teenagers in Indonesia, which is caused by various factors such as lack of knowledge about reproductive health, the influence of socializing, and technological advances that facilitate access to sexual information. Based on the results of an initial survey of students at SMAN 1 Batuan, it was found that 60% of them did not fully understand the dangers, factors, impacts, and prevention of free sex. For this reason, Community Service activities were carried out through the